Validation of the brief physical activity assessment tool: Comparison of telephone and in-person administration - Rui Vilarinho; Liliana Amorim; Diana Gomes; Pedro Teixeira; Ana Alves da Silva; Janete Santos; Filipa Bernardo; Jaime Correia de Sousa; João Almeida Fonseca; Cristina Jácome (PLoS ONE, 2025)
We examined the reliability and validity of the Brief Physical Activity Assessment Tool (BPAAT) when administered by telephone interview compared to in-person administration. We analyzed data from the Epi-asthma study. Adult participants registered in the participating Portuguese primary health care centres (PCC) completed the BPAAT via telephone. After ~3 days (range 0–5 days), they had a face-to-face visit at their PCC and completed BPAAT using a tablet. The BPAAT classify individuals as "insufficiently active" (score 0–3) or "sufficiently active" (score 4–8). 355 subjects (60.8% female, 54[IQR 42–66] years) were included. The median BPAAT score was 2[0–4] for both methods, with a significant correlation (rho = 0.58, p<0.001). Test-retest reliability was moderate (ICC = 0.56, 95%CI 0.49–0.63). Agreement in physical activity classification was fair (71.5%, kappa = 0.31, 95%CI 0.21–0.41), with telephone administration classifying more individuals as "sufficiently active" (37.2%) than in-person (15.5%). Telephone administration of the BPAAT is a valid and reliable approach for monitoring of physical activity in the general population. However, it may slightly overestimate activity levels compared to face-to-face administration, particularly among subjects aged 65 years and older.